The frontier within : essays by Abe Kōbō - Abe, Kōbō, 1924-1993 (Columbia University Press, 2013)
Abe Kobo (1924-1993) was one of Japan's greatest postwar writers, recognized widely for his science fiction and plays of the absurd. He also wrote keen theoretical criticism for which he is lesser known, merging literary, historical, and philosophical perspectives. From the nature of creativity to the evolution of the human species, Abe tackled contemporary social issues and literary theory with the depth and facility of a visionary thinker.
Keywords: Abe, Kōbō, -- 1924-1993 -- Translations into English.; Abe, Kōbō, -- 1924-1993; LITERARY CRITICISM -- Asian -- General.; HISTORY -- Essays.; Japanese literature; Essay; Japanisch; Electronic books.; Libros electronicos.; essays.; Translations; Essays; Essays.; Essais.